HUBUNGAN PENGUASAAN MATERI THAHARAH DENGAN KESADARAN MENJAGA KEBERSIHAN SEBAGAI ACUAN MANAJEMEN LINGKUNGAN SEKOLAH - Fikri, Achmad Ali; Bustomi, Muhammad Farid; Nikmah, Astitik (QUALITY, 2019)
This study aims to determine the mastery of student subject matter, the awareness of maintaining cleanliness of the school environment, and the relationship of mastery of student subject matter with the awareness of maintaining hygiene as a reference for school environment management. The population was 125 students of class VII MTs Hasan Kafrawi Jepara and a sample of 70 students with random sampling. Using a quantitative approach to the technique of collecting test data, questionnaires, and observations. Then using description analysis and correlation analysis. The results showed the value of r arithmetic = 0.431 means r arithmetic> r table (0.431> 0.235) This shows that there is a positive and significant relationship between mastery of student subject matter with awareness of maintaining cleanliness. This can be used as a reference for environmental management in MTs Hasan Kafrawi  Jepara.